1978
DOI: 10.1037/0022-006x.46.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological stability in multiple sclerosis.

Abstract: The neuropsychological performances of 14 patients who had multiple sclerosis (MS) and who received repeated testings spaced over time by at least 1 year were compared with identical evaluations of 14 patients who had neurological involvement but not MS. Subjects in each group were individually matched on chronological age at first testing, length of test-retest interval, sex, and years of formal education. Performance decrements attributable to the demyelination process of MS were primarily manifested on task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…Findings suggestive of a decline in intellectual functions were also observed in a longitudinal study by Ivnik (1978b). He matched 14 patients with MS to 14 patients with verified brain damage of various etiologies on age and education.…”
Section: Intelligencementioning
confidence: 76%
See 1 more Smart Citation
“…Findings suggestive of a decline in intellectual functions were also observed in a longitudinal study by Ivnik (1978b). He matched 14 patients with MS to 14 patients with verified brain damage of various etiologies on age and education.…”
Section: Intelligencementioning
confidence: 76%
“…Using the Wechsler scales, several studies have compared the performance of MS patients to that of various control groups, including normals (Jambor, 1969, Parsons, Stewart, & Arenberg, 1957Reitan, Reed, & Dyken, 1971), brain-damaged patients (Goldstein & Shelly, 1974;Ivnik, 1978b, Jambor, 1969, non-brain-damaged, neurologically disabled patients (Jambor, 1969), and psychiatric patients (Goldstein & Shelly, 1974;Jambor, 1969). These studies are noteworthy for the lack of significant mean group differences both for the IQ and individual subtest scores.…”
Section: Intelligencementioning
confidence: 96%
“…An obvious limitation of these findings is that the data from the NP tests were obtained 1 to 2 years before the coping measures. Although this is a potential problem, it should be noted that performance by MS patients on tests that do not have a substantial sensory-motor component remains stable or shows only a slight decline for test-retest intervals of up to 3 years (Bernardin, 1992;Ivnik, 1978). Even if one assumes some decline in test performance over the period of our study, there is no reason to predict a systematic change in the relative ranking of the patients' performances on the various tests.…”
Section: Discussionmentioning
confidence: 98%
“…Language disorders are rarely reported in MS [54]. According to Feinstein [17], agnosia, apraxia, and language difficulties are absent or mild in MS. Ivnik [18] reported that verbal skills were relatively intact during a 3-year follow-up period. Caine et al [14], Rao et al [5] and Achiron et al [15] found that verbal fluency was affected in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ivnik [18] found that verbal skills remained relatively intact, whereas psychomotor performance deteriorated during a 3-year follow-up period. The cognitive longitudinal dysfunction may also be selective in terms of disease course [19].…”
Section: Introductionmentioning
confidence: 99%